The Effectivity of Using Suggestopedia in Improving Learning Outcomes and Speaking Skills in Elementary Schools: A Literature Review - Rahma, Septia Najwa; Laila Nurul Karima; Siagian, Olivia Veronica; Nusu, Okta Efagriana (Candradimuka: Journal of Education, 2025)
The Suggestopedia method is a learning approach that emphasizes a relaxed and fun learning atmosphere, supported by elements of music, relaxation, and games. This article presents the results of a literature review of several studies that tested the effectiveness of the Suggestopedia method in improving language learning outcomes. These studies were conducted at different levels of education, from primary education to higher education, in different countries. The results show that the Suggestopedia method significantly improves students' learning activities, speaking skills, and comprehension of language materials, especially in English language learning. Furthermore, the integration of information and communication technology (ICT) into the Suggestopedia method is proven to increase the effectiveness of this method in language teaching, especially in improving students' pronunciation and comprehension. In conclusion, Suggestopedia with the support of technology and media can have a significant positive impact on learning outcomes and student attitudes towards the learning process.